Swastika Philosophy and Corporate Sustainability: A Stakeholder Perspective - Ida Bagus Ketut Bayangkara (Jurnal Ilmiah Akuntansi dan Bisnis, 2026)
This study investigates the philosophical values of Swastika as the foundational spirit for corporate sustainability and examines vertical-horizontal relationship patterns as a model for stakeholder engagement. Adopts a phenomenological approach, through in-depth interviews with thirteen Swastika users and two state-owned enterprise directors involved in sustainability, the research uncovers their lived experiences. Data analysis involved textual and structural descriptions, culminating in the identification of essential invariants. Findings reveal Swastika’s values as both the guiding spirit and an operational framework for sustainable corporate practices, emphasizing stakeholder definitions rooted in shared well-being. These insights contribute to the academic field by enriching sustainability theory, provide a novel reference for advancing sustainability efforts, particularly in formulating stakeholder values to enhance strategic development and maximize stakeholder contributions. The study’s original contributions include the articulation of stakeholder categories, the embodiment of Swastika’s sustainability spirit, and its practical application within corporate sustainability is novelty elements not previously disclosed.